Factors linked with the modification of mental health score of Peruvian personnel in Machu Picchu Antarctica base - Alvarez-Risco, Aldo (2024)
[Introduction]: Isolation of people needs significant support, potentially impacting their mental well-being for future assignments. [Objective]: This study aimed to examine whether the military institution or other factors were associated with changes in the mental health of Peruvian navy and army personnel in Antarctica. [Methods]: The exploratory study employed a prospective cohort design, conducting surveys at two different points during the trip. Various factors such as stress, anxiety, depression (measured using DASS-21), and post-traumatic stress (measured using SPRINT-E) were assessed, alongside other variables. [Results]: The outcomes indicated noteworthy changes in the participants’ scores. Specifically, stress scores increased among navy personnel but decreased in the army. Moreover, anxiety scores decreased among those with previous trips and increased among those without. Additionally, anxiety scores remained stable in the navy but decreased in the army. Furthermore, depression scores increased in the navy and decreased in the army. The study also found that older age was associated with higher post-traumatic stress scores. Additionally, posttraumatic stress scores decreased among those with technical studies and increased among those with university studies. [Conclusion]: The exploratory findings suggest that the institution to which the personnel belonged and other characteristics of the delegations may be linked to changes in the scores of the evaluated mental health factors. These findings could offer valuable insights for future delegations facing similar conditions. Future studies should increase the sample size to allow for a more detailed analysis of the effects and to enhance the generalizability of the findings.